THE HERZEGOVINIAN UPRISING ACCORDING TO THE MEMORIES OF ALBIN HUGO KUTSCHBACH - Стојанка Лужија (Srpski Istorijski Časopis)
After the outbreak of the uprising in Herzegovina (1875), the idea of a final solution to the Eastern Question seemed feasible. Volunteers, mainly from the Austro-Hungarian Empire, but also from other European countries, began to arrive in Herzegovina. The young German Albin Hugo Kutschbach arrived first in Montenegro and then in Herzegovina during the summer of the same year. Having joined the insurgent movement, he personally participated in the insurgents’ war operations. In his later years, he wrote memoirs in which, among other things, he recalled his years in the uprising. The aim of this paper is, through analyze his memories during two years of the warfare, to examine the development of the uprising, the organization of the uprising movement itself, as well as the relationship between Montenegro, on the one hand, and the insurgents and their leaders, on the other. The author’s personal testimonies are also an advantage in this regard, because Kutschbach’s memoirs as a narrative historical source, despite all their limitations, are a valu able source of data for the Herzegovina Uprising.